Kemitraan Bidan dan Ibu Hamil dalam Pencegahan Covid-19 - Simbolon, Juana Linda; Sitompul, Emilia Silvana; Siregar, Marni (Direktorat Penelitian dan Pengabdian kepada Masyarakat (DPPM), 2021)
COVID-19, a disease that is currently endemic in almost all over the world. COVID-19 affects anyone, including pregnant women and children. The role of midwives in maternal and child health services: ANC service providers are the highest in Indonesia (82.4%). The challenge of midwifery services during the Covid-19 pandemic: knowledge of mothers and families related to COVID-19 about the dangers of COVID-19 in pregnant women can be a motivation for screening or preventing COVID-19. The aim of the service is to increase knowledge through training midwives and pregnant women about the prevention of COVID-19 and to increase partnerships between midwives and pregnant women through training to be able to socialize the importance of preventing COVID-19 to pregnant women. The method used was conducting pre-tests for midwives and pregnant women, training for midwives on the prevention of COVID-19 in pregnant women, counseling by midwives on prevention of COVID-19, and conducting post-tests. The results obtained by pre test, the majority of midwives' knowledge was moderate, while the majority of pregnant women had less knowledge. After being given training, the results of the post test increased the majority of midwives' knowledge was high and the knowledge of pregnant women was high.